2010
DOI: 10.1002/nau.20950
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thoracic epidural analgesia on lower urinary tract function in women

Abstract: TEA has a significant effect on bladder emptying with clinically relevant postvoid residual (PVR) necessitating (indwelling or intermittent) catheterization or monitoring of PVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…36,50,63,64 most trials examining PouR in patients undergoing abdominal surgery with epidural analgesia conclude that catheters should be removed on PoD 1. [65][66][67][68][69] CONCLUSION the practice of earlier urinary catheter removal must be balanced with the perioperative factors of intraoperative fluid volume and oRt to avoid high urinary retention rates. if early catheter removal is used in postoperative care, it is important also to have protocols in place to detect urinary retention early given the potential sequelae of unrecognized bladder overdistension, which include prolonged catheter drainage and increased risk for uti, the need for additional outpatient visits for voiding trials, and even bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…36,50,63,64 most trials examining PouR in patients undergoing abdominal surgery with epidural analgesia conclude that catheters should be removed on PoD 1. [65][66][67][68][69] CONCLUSION the practice of earlier urinary catheter removal must be balanced with the perioperative factors of intraoperative fluid volume and oRt to avoid high urinary retention rates. if early catheter removal is used in postoperative care, it is important also to have protocols in place to detect urinary retention early given the potential sequelae of unrecognized bladder overdistension, which include prolonged catheter drainage and increased risk for uti, the need for additional outpatient visits for voiding trials, and even bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to our previous studies, where a significant increase in postvoid residuals could be demonstrated after open renal surgery. 2,3 Explanations could be differences in IPSS, age, type of surgery performed, or the level of insertion of the epidural catheter.…”
Section: Discussionmentioning
confidence: 99%
“…3 These findings suggest that postvoid residuals should be monitored under TEA or a transurethral catheter left in place after open renal surgery via lumbotomy. Based on the fact that these studies adopted a before-after design, we could not make conclusions concerning the mechanisms that were responsible for bladder dysfunction.…”
mentioning
confidence: 95%
“…A caudal epidural (also referred to as a sacral‐coccygeal or coccygeal epidural) is an alternative anesthetic and analgesic protocol that, in people, results in maximal urethral relaxation while providing analgesia to the urogenital tract with minimal systemic side effects 12,13 . Caudal epidurals are routinely performed in people, 13,14 horses, 15 cows, 16 dogs, 17 and less frequently in cats 18 .…”
Section: Introductionmentioning
confidence: 99%
“…11 A caudal epidural (also referred to as a sacral-coccygeal or coccygeal epidural) is an alternative anesthetic and analgesic protocol that, in people, results in maximal urethral relaxation while providing analgesia to the urogenital tract with minimal systemic side effects. 12,13 Caudal epidurals are routinely performed in people, 13,14 horses, 15 cows, 16 dogs, 17 and less frequently in cats. 18 A caudal epidural block results in regional anesthesia to the perineum, penis, urethra, colon, and anus by blocking the pudendal, pelvic, and caudal nerves while motor function to the hind limbs is maintained.…”
mentioning
confidence: 99%